Interpreting Horace in Th. Zielinski’s and M. Rostovtzeﬀ’s Critique of I. Grevs - Keyer, Denis (Hyperboreus, 2021)
I. Grevs’ study of Horace’s Sabine estate (Grevs 1899) was reviewed by Zielinski 1900a, who made astute critical objections along with eloquent remarks on the unity of historical-philological method. In particular, he showed that Grevs’ conclusions on the existence of vineyards and olive plantations in the estate was drawn from controversial interpretations of Epist. 1. 16, 1. 14 and 1. 8. M. Rostovtzeﬀ’s famous monograph (Rostovtzeﬀ 1926) displays Horace’s Sabinum as a typical medium-sized estate with reference to Grevs 1899; he follows Grevs in treating the part of the estate run by Horace himself as a diversiﬁed farm that cultivated vines along with fruit and vegetable gardens, thus ignoring Zielinski’s objections and possibly exaggerating the diversiﬁed commercial production of the Sabinum.